2022
DOI: 10.3389/fenrg.2022.956280
|View full text |Cite
|
Sign up to set email alerts
|

A prediction on the impacts of China’s national emissions trading scheme on CO2 emissions from electricity generation

Abstract: One of the government policies that can reduce CO2 emissions is the Emissions Trading Scheme (ETS), which was implemented in the Chinese economy on 16 July 2021. It is the largest ETS in the world, covering 12% of global CO2 emissions. Since this policy has not been experienced in China, it is necessary to predict its impact on CO2 emissions in this country. Furthermore, electricity and heat production is the major contributor to total CO2 emissions from fuel combustion. Therefore, this study attempts to predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Using the ARDL model, Solaymani [45] argued that in response to increases in GDP, carbon intensity, and energy intensity, CO 2 emissions increase substantially. A vector autoregression investigation result showed that GDP is one of the key drivers of CO 2 emissions in Chinese power plants in the short and long run [46]. Pejović et al [47], using Panel VAR, showed that renewable energy can stimulate environmental quality, and the variations in GDP largely determine the majority of changes in CO 2 emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using the ARDL model, Solaymani [45] argued that in response to increases in GDP, carbon intensity, and energy intensity, CO 2 emissions increase substantially. A vector autoregression investigation result showed that GDP is one of the key drivers of CO 2 emissions in Chinese power plants in the short and long run [46]. Pejović et al [47], using Panel VAR, showed that renewable energy can stimulate environmental quality, and the variations in GDP largely determine the majority of changes in CO 2 emissions.…”
Section: Literature Reviewmentioning
confidence: 99%